Development of a web-based application to contribute to the conservation of wildlife species in UTM campus [electronic resource] - Muhamad Firdaus Johan, 1990-; Soheil Sabri, supervisor; Ariva Sugandi Permana, supervisor (2014)
Project Paper (Sarjana Muda Perancangan dan Wilayah) - Universiti Teknologi Malaysia, 2014